Perubahan Harga, Volume Saham, dan Kapitalisasi Pasar Selama COVID-19 pada Sektor Keuangan - Joanna Yutanesy; Rousilita Suhendah (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
The purpose of this study is to analyze about the difference of stock prices, stock trading volume, and market capitalization before and during the COVID-19 outbreak on the financial sector listed on the Indonesia Stock Exchange during January 1, 2020 until April 30, 2020 period. The research design is a descriptive study and double regression. This study used a purposive sampling method, which is a non probability sampling, amounted to 100 financial companies. The hypothesis testing is done by Wilcoxon signed rank test, a non parametric statistic test. This study used SPSS 26th versions software. The result shows that there is a significant negative difference of stock price, stock trading volume, and market capitalization before and during the COVID-19 outbreak on the financial sector. Furthermore, this study shows that there is no significant difference of stock trading volume before and during the COVID-19 outbreak on the financial institution subsector.